Validation and Psychometric Properties of the Minnesota Living With Heart Failure Questionnaire in Individuals With Coronary Artery Disease in Lithuania - Gecaite-Stonciene, Julija; Burkauskas, Julius; Bunevicius, Adomas; Steibliene, Vesta; Macijauskiene, Jurate; Brozaitiene, Julija; Mickuviene, Narseta; Kazukauskiene, Nijole (Frontiers in Psychology, 2022)
Background Health-related quality of life (HRQoL) is known to be impaired in individuals with coronary artery disease (CAD), especially in those after a recent acute coronary syndrome (ACS). Heart failure (HF) is a common burden in this population that significantly contributes to worsening HRQoL. To accurately measure the level of HRQoL in individuals with CAD after ACS, disease-specific scales, such as the Minnesota living with heart failure questionnaire (MLHFQ), are recommended. Nevertheless, to date, there has not been a study that would comprehensively evaluate the psychometric properties of the MLHFQ in a large sample of individuals with CAD after ACS. The debate regarding the internal structure of MLHFQ is also still present. Hence, this study aimed to translate the MLHFQ and evaluate its internal structure, reliability/precision, and validity in individuals with CAD following ACS in Lithuania. Methods In the cross-sectional study, 1,083 participants (70% men, age M = 58, SD = 9) were evaluated for sociodemographic and clinical characteristics. HRQoL was measured using the MLHFQ and the Short Form-36 health survey (SF-36). In addition, exercise capacity (EC) was also evaluated in the study patients, using a standardized computer-driven bicycle ergometer. Results The internal consistency of the MLHFQ subscales (0.79−0.88) was found to be good. Confirmatory factor analysis (CFA) provided the support for the three-factor model (“physical domain,” “social domain,” and “emotional domain”) of the MLHFQ and showed acceptable fit [comparative fit indices (CFI) = 0.894; goodness-of-fit (GFI) = 0.898; non-normal fit index (NFI) = 0.879, and root mean square error of approximation (RMSEA) = 0.073]. Regarding convergent evidence, significant associations were found between the MLHFQ domains and the SF-36 domains and EC (r’s range 0.11−0.58). Conclusion The current study completed cultural validation and provided further information on the psychometric characteristics of the MLHFQ in Lithuania, suggesting MLHFQ as a valid and reliable instrument to measure HRQoL. The Lithuanian version of MLHFQ is best described by a three-factor solution, measuring physical, social, and emotional dimensions of HRQoL among individuals with CAD following ACS.